Human Activity as a Growing Threat to Marine Ecosystems: Plastic and Temperature Effects on the Sponge Sarcotragus spinosulus - Jessica Lombardo; Maria del Mar Ribas-Taberner; Maria Magdalena Quetglas-Llabrés; Samuel Pinya; Llorenç Gil; Silvia Tejada; Antoni Sureda; Montserrat Compa (Toxics)
Human activities increasingly threaten marine ecosystems through rising waste and temperatures. This study investigated the role of plastics as vectors for Vibrio bacteria and the effects of temperature on the marine sponge Sarcotragus spinosulus. Samples of plastics and sponges were collected during July, August (high-temperature period), and November (lower-temperature period). Bacterial growth and sponge responses were analysed using biochemical biomarkers. The results revealed a peak in colony-forming units (CFU), particularly of Vibrio alginolyticus, on plastics and sponges in August, followed by a decrease in November. In August, CFU counts of Vibrio spp. were significantly higher in sponges with poor external appearance (characterized by dull coloration and heavy epiphytic growth) but returned to levels observed in healthy sponges by November. Microplastics were detected in the tissues of both sponge groups, with higher concentrations found in affected specimens. Biomarker analyses revealed increased lysozyme, glutathione S-transferase, catalase, and superoxide dismutase activities in healthy sponges during August, while malondialdehyde levels, indicating oxidative damage, were higher in affected sponges. In conclusion, affected sponges exhibited elevated CFU counts of Vibrio spp. and reduced antioxidant and detoxification responses under elevated temperatures. These findings suggest that combined impacts of plastics and warming may pose significant risks to S. spinosulus in the context of global climate change.